Multiparameter-analysis of CO2/Steam-enhanced gasification and pyrolysis for syngas and biochar production from low-cost feedstock - Rafael B.W. Evaristo (Elsevier, 2021)
The disposal of spent coffee grounds (SCG) and brewers' spent grains (BSG) has become an environmental issue. Thus, the waste-to-energy valorization of these two low-cost feedstocks was performed via gasification and pyrolysis to assess their potential as syngas and biochar fuels. The processes’ optimum conditions were investigated by a multiple-criteria decision support method. Firstly, both raw materials were gasified at 1000 °C with O2/N2, O2/CO2/N2 and O2/H2O/N2 atmospheres. The characteristics and energy performance of the producer gas were evaluated. In addition, the exergy analysis of green-H2 production was assessed. The pyrolysis experiments were conducted at 300, 500 and 700 °C, followed by a comprehensive characterization of the biochar properties and its combustion behavior. The syngas production based on CO2/Steam-enhanced gasification has indicated clear energetic and exergetic improvements against O2/N2 with a promising increase of 32.97% LHVsyngas for BSG. Obtained biochar possesses favorable fuel characteristics promoting an HHV enhancement up to 19.42% (SCG) and 83.11% (BSG). Furthermore, the combustion index indicated a great potential of using SCG and BSG as solid biofuel for straightforward application to heat generation in small-scale systems. Therefore, syngas and biochar characteristics encourage feasible biofuels from low-cost feedstocks for energy generation.